"Technology has allowed us to do a lot more but it's not necessarily the panacea for everybody": Family physician perspectives on virtual care during the COVID-19 pandemic and beyond. - Lindsay Hedden; Sarah Spencer; Maria Mathews; Emily Gard Marshall; Julia Lukewich; Shabnam Asghari; Paul Gill; Rita K McCracken; Crystal Vaughan; Eric Wong; Richard Buote; Leslie Meredith; et al. (PLoS ONE, 2024)
Introduction Early in the COVID-19 pandemic, Canadian primary care practices rapidly adapted to provide care virtually. Most family physicians lacked prior training or expertise with virtual care. In the absence of formal guidance, they made individual decisions about in-person versus remote care based on clinical judgement, their longitudinal relationships with patients, and personal risk assessments. Our objective was to explore Canadian family physicians' perspectives on the strengths and limitations of virtual care implementation for their patient populations during the COVID-19 pandemic and implications for the integration of virtual care into broader primary care practice. Methods We conducted semi-structured qualitative interviews with family physicians working in four Canadian jurisdictions (Vancouver Coastal health region, British Columbia; Southwestern Ontario; the province of Nova Scotia; and Eastern Health region, Newfoundland and Labrador). We analyzed interview data using a structured applied thematic approach. Results We interviewed 68 family physicians and identified four distinct themes during our analysis related to experiences with and perspectives on virtual care: (1) changes in access to primary care; (2) quality and efficacy of care provided virtually; (3) patient and provider comfort with virtual modalities; and (4) necessary supports for virtual care moving forward. Conclusions The move to virtual care enhanced access to care for select patients and was helpful for family physicians to better manage their panels. However, virtual care also created access challenges for some patients (e.g., people who are underhoused or living in areas without good phone or internet access) and for some types of care (e.g., care that required access to medical devices). Family physicians are optimistic about the ongoing integration of virtual care into broader primary care delivery, but guidance, regulations, and infrastructure investments are needed to ensure equitable access and to maximize quality of care.